2021
DOI: 10.1002/curj.134
|View full text |Cite
|
Sign up to set email alerts
|

Songs and singing songs in early childhood education: A review of Spanish curriculum policy

Abstract: This paper aims to explore Spanish curriculum policy related to song in early childhood education. By means of a document analysis, the different state governments' guidelines were reviewed. Song and singing songs are included in the official documents as curriculum content, as a pedagogical tool to approach curriculum content, and as an activity that helps promote personal and social development. In the first case, song is associated with the interpretative, aesthetic or artistic values to be enhanced in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This finding may be attributed to the difficulty in drawing boundaries among the disciplines considered in interdisciplinary studies (Fllis & Fouts, 2001). Another notable finding of this study is that even though music is considered core content in early childhood in many countries (Campbell & Scott-Kassner, 2010; Casal de la Fuente & Gillanders, 2022; McDonel, 2015; Polat, 2018), few academic studies have been conducted on the integration of music in preschool contexts. This finding may be supported by Barboros and Akbulut’s (2021) study, which has shown that preschool teachers in Turkey are incompetent in implementing the goals of music instruction.…”
Section: Discussionmentioning
confidence: 86%
“…This finding may be attributed to the difficulty in drawing boundaries among the disciplines considered in interdisciplinary studies (Fllis & Fouts, 2001). Another notable finding of this study is that even though music is considered core content in early childhood in many countries (Campbell & Scott-Kassner, 2010; Casal de la Fuente & Gillanders, 2022; McDonel, 2015; Polat, 2018), few academic studies have been conducted on the integration of music in preschool contexts. This finding may be supported by Barboros and Akbulut’s (2021) study, which has shown that preschool teachers in Turkey are incompetent in implementing the goals of music instruction.…”
Section: Discussionmentioning
confidence: 86%
“…Many school curriculums insert song and singing activities to enhance the learning experience. A document analysis review of Spanish curriculum policy showed the importance of songs and singing songs in early childhood education to language learning acceleration, cultivate cultural understanding, and enhance social skills [1]. Another study in Indonesia showed a positive correlation between children's songs and the ability to memorize foreign vocabulary in kindergarten, supporting the notion of children's songs as a learning strategy in language learning [2].…”
Section: Introductionmentioning
confidence: 97%